Reovirus type-2 infection in newborn DBA/1J mice reduces the development of late allergic asthma - Nakashima, Tomomi; Hayashi, Toshiharu; Mizuno, Takuya (International journal of experimental pathology, 2012)
Summary The aim of the present study was to determine whether or not the development of a helper T (Th) 1 response induced by Reovirus type‐2 (Reo‐2) infection would protect against the development of Th2‐mediated late allergic asthma. This hypothesis was examined by infecting one day old neonatal DB A/1J mice with Reo‐2 in an ovalbumin (OVA)‐induced late asthma model. Compared with the controls (either infected or uninfected mice with or without OVA sensitization and/or OVA challenge), Reo‐2 infection lessened the magnitude of the subsequent allergic Th2‐mediated late asthma. In infected mice with allergic late asthma, there was decreased infiltration of interleukin (IL)‐4+, IL‐5+, IL‐13+ and very late antigen (VLA)‐4+ lymphocytes, and eotaxin‐2+ and VLA‐4+ eosinophils, in both bronchial and bronchiolar lesions. Also the expression of vascular cell adhesion molecule (VCAM)‐1 and eotaxin‐2 on vascular endothelial cells was reduced. Moreover, the systemic production of IL‐4, IL‐5, tumour necrosis factor‐α and OVA‐specific IgE was reduced, whereas systemic IFN‐γ production was increased. In addition, there was no increase in IFN‐α production. Thus the present study suggests that systemic Reo‐2 infection at birth may reduce the development of subsequent late allergic asthma by the induction of a Th1 response. Therefore the potential suppressive mechanism(s) that might be induced by Reo‐2 infection in newborn mice and their effects on the development of late allergic asthma are discussed.